ONLINE INFORMAL LEARNING OF ENGLISH AND MOTIVATION TO LEARN EFL: CORRELATIONAL STUDY - Kamal, Musthafa; Ramadhan, Rizki; Dibdyaningsih, Haris (JOEEL (Journal of English Education and Literature), 2021)
The trend of online learning has been intensifying and present is the need for study to align this phenomenon to motivation in order for language teachers to boost students achievement. This research is about to inquire the correlation between online informal learning of English and motivation to learn English. Quantitative method was used to measure the correlation between variables. Subjects were students in a boarding school selected with random sampling. To obtain data, questionnaire and interview were conducted. There were 55 students in total that participated in completing the questionnaire and only 16 of them were taken to be considered for the interview. The questionnaire was in Likert Scale about the frequency of English use and about the motivation in learning. Semi-structured interview was used to confirm and expand the data. Statistical analysis of two questionnaire resulted in a positive correlation (correlation coefficient {r} = 0,48). This means that higher values of one variable tend to be associated with higher values of other variable. Suggestion was to increase English use in online activities, to observe other factors affecting the results, and more research is needed to be conducted.